Education on High-Risk Pregnancy and Nutritional Monitoring of Pregnant Women to Prevent Stunting: High-Risk Pregnancy Education and Stunting Prevention - Nurhikmah; Muliyana; Uli, Evawaty; Tahir, Dyah; Erwin (Journal of Evidence-Based Community Health, 2026)
Stunting remains a major public health problem in Indonesia, particularly in rural areas, and prevention efforts must begin during pregnancy. This community service program aimed to improve knowledge and awareness regarding high-risk pregnancy and maternal nutritional monitoring as an early strategy to prevent stunting in Tupabiring Village. The program was conducted using a structured approach consisting of preparation, implementation, and evaluation stages. Activities included health education sessions, interactive discussions, nutritional status assessment through body weight and mid-upper arm circumference (MUAC) measurements, anemia risk identification, and individualized counseling for pregnant women. The results showed an improvement in participants’ knowledge of high-risk pregnancy, danger signs, balanced maternal nutrition, and the importance of routine antenatal care (ANC) visits. Nutritional monitoring enabled early identification of pregnant women at risk of nutritional problems, providing a basis for targeted counseling and follow-up recommendations. The involvement of family members and community health cadres strengthened community participation and program sustainability. In conclusion, education combined with maternal nutritional monitoring is an effective community-based intervention to enhance maternal health awareness and support early stunting prevention efforts. Sustainable and integrated programs at the village level are recommended to optimize long-term maternal and child health outcomes